Ultrafast high-resolution magic-angle-spinning NMR spectroscopy1. Issue 12 (21st June 2015) - André, Marion; Piotto, Martial; Caldarelli, Stefano; Dumez, Jean-Nicolas
<x xml:space="preserve">Abstract</x> The acquisition of ultrafast high-resolution magic-angle spinning (HR-MAS) NMR spectra of semi-solid samples is demonstrated.